2010
DOI: 10.1016/j.jconrel.2010.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in vivo gene expression mediated by listeriolysin O incorporated anionic LPDII: Its utility in cytotoxic T lymphocyte-inducing DNA vaccine

Abstract: Enhanced in vivo gene expression using non-viral vectors is a critical issue in gene therapy in general. Among the many potential utilities of non-viral vector-mediated gene delivery, its application in DNA-based vaccination is an attractive approach with several practical advantages over conventional vaccination. We have previously shown that the endosomolytic bacterial protein listeriolysin O (LLO) is capable of facilitating transfection in vitro using the LPDII (anionic liposome-polycation-DNA complexes) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…An anionic liposome-polycation-DNA complex combined with LLO was used as vaccine by Sun and colleagues to deliver OVA-cDNA. This formulation produced an enhanced CD8 + T-cell response, higher CTL frequency and IFNγ production after stimulation by an OVA-specific peptide [Sun et al 2010]. Andrews and colleagues analyzed whether encapsulating CpGs in LLO liposomes would enhance cell-mediated immune response and skew T H 1-type responses in a protein antigenbased vaccine utilizing LLO liposomes.…”
Section: Listeriolysinmentioning
confidence: 99%
“…An anionic liposome-polycation-DNA complex combined with LLO was used as vaccine by Sun and colleagues to deliver OVA-cDNA. This formulation produced an enhanced CD8 + T-cell response, higher CTL frequency and IFNγ production after stimulation by an OVA-specific peptide [Sun et al 2010]. Andrews and colleagues analyzed whether encapsulating CpGs in LLO liposomes would enhance cell-mediated immune response and skew T H 1-type responses in a protein antigenbased vaccine utilizing LLO liposomes.…”
Section: Listeriolysinmentioning
confidence: 99%
“…Kyung-Dall Lee and coworkers were the first to report on the ability of this protein to enhance cytosolic delivery of engineered nanocarriers [120]. Since then, LLO has been used in a number of investigations to enhance the delivery of biological macromolecules, including lipid-encapsulated proteins [121, 122], as well as lipoplexes [123, 124] and polyplexes for gene delivery [125-127]. More recently, mutants of the LLO protein with enhanced pore-forming activity have been identified, allowing lower concentrations of LLO to be used in macromolecular delivery formulations, thereby enhancing endosomal escape while reducing cytotoxicity [128].…”
Section: Design Strategies To Achieve Endosomal Escapementioning
confidence: 99%
“…Recently, one study demonstrated that an LLO-containing LPDII-DNA delivery system works effectively for DNA delivery and leads to efficient DNA priming through the adoption of a DNA primeprotein boost vaccination protocol. 113 These researchers used OVA as a model antigen and found that the incorporation of LLO into the LPDII gene delivery system heightened gene expression in vitro and enhanced OVA-specific CD8 + CTL responses in vivo. 113 The results of the study may imply that the design of an LLOcontaining LPDII delivery system for DNA-based vaccines to stimulate protective immunity against diseases, such as cancer, has noteworthy value for future research.…”
Section: Llo-based Anti-tumor Vaccine Developmentmentioning
confidence: 99%
“…113 These researchers used OVA as a model antigen and found that the incorporation of LLO into the LPDII gene delivery system heightened gene expression in vitro and enhanced OVA-specific CD8 + CTL responses in vivo. 113 The results of the study may imply that the design of an LLOcontaining LPDII delivery system for DNA-based vaccines to stimulate protective immunity against diseases, such as cancer, has noteworthy value for future research. Bacteria and their components, such as lipoteichoic acid (LTA), lipopolysaccharide (LPS), and CpG motifs, are some of the most potent inducers of DC maturation and can be easily sensed by the innate immune system.…”
Section: Llo-based Anti-tumor Vaccine Developmentmentioning
confidence: 99%